The nuclear tipping point : why states reconsider their nuclear choices - Campbell, Kurt M., 1957-; Einhorn, Robert J.; Reiss, Mitchell (Brookings Institution Press, 2004)
More than half a century after the advent of the nuclear age, is the world approaching a tipping point that will unleash an epidemic of nuclear proliferation? Today many of the building blocks of a nuclear arsenal--scientific and engineering expertise, precision machine tools, software, design information--are more readily available than ever before. The nuclear pretensions of so-called rogue states and terrorist organizations are much discussed. But how firm is the resolve of those countries that historically have chosen to forswear nuclear weapons? A combination of changes in the international.